Energy-Efficient Virtual Machine Migration and Consolidation Algorithm in Cloud Data Center - Hongjian Li; Yu Dai; Rui Liu; Yi Jiang (Dianxin kexue)
An energy-efficient virtual machine（VM）migration and consolidation algorithm with multi-resource was proposed. The algorithm was developed based on a multi-resource energy efficiency model. A method of multi-resource utilization double threshold was designed to trigger migration of virtual machine, and the optical particle swarm optimization method was introduced in the consolidation of virtual machine. Compared with traditional heuristic algorithms, the algorithm reduces the number of active physical nodes and the amount of VM's migration effectively, and obtains better energy efficiency in cloud data center.